One-stage En bloc resection of thoracic spinal chondrosarcoma with huge paravertebral mass through the single posterior approach by dissociate longissimus thoracis - Xu, Wei; Ye, Chen; Zhang, Dan; Wang, Peng; Wei, Haifeng; Yang, Xinghai; Xiao, Jianru (Frontiers in Surgery, 2022)
Study design Retrospective case series. Objective To describe the technique details and therapeutic outcomes of 3-D printing model-guided en bloc resection of chondrosarcoma (CHS) with huge paravertebral mass via the combined posterior median and Wiltse approach. Summary of background data Total en bloc spondylectomy (TES) technique is conventionally based on the single posterior approach or combined anterior-posterior approach. However, the single posterior approach imposes a high technical demand on the surgeon due to the narrow field of vision, limited surgical space and the delicate spinal cord, while the combined anterior-posterior approach not only requires greater patient tolerance but is time consuming and runs the risk of more blood loss and injury to the visceral pleura and large blood vessels during surgery. In addition, it is difficult to completely remove the thoracic CHS with paravertebral mass through simple en bloc resection when it involves the aorta, vena cava, costa and lung. Material and methods Between August 2010 and January 2016, we performed a retrospective study to evaluate the clinical characteristics and outcomes of en bloc resection of thoracic spinal CHS with paravertebral mass through the combined posterior median and Wiltse approach. Postoperative recurrence-free survival (RFS) and overall survival (OS) were estimated by the Kaplan-Meier method. P values less than 0.05 were considered statistically significant. Results Altogether 15 patients received en bloc resection of thoracic spinal CHS with paravertebral mass through the combined posterior median and Wiltse approach. The mean age of these patients was 37.0 ± 12.8 years (median 36; range 15–64). This combination approach provided more extensive exposure and wider marginal resection of the tumor within a mean operation duration of 288 ± 96 min (median 280; range 140–480) and mean intraoperative blood loss of 1,966 ± 830 ml (median 2,000; range 300–3,000). Of the 15 patients, 5 experienced local recurrence of the disease; the mean time from surgery to recurrence was 22 ± 9.85 months (median 17, range 13–35). RFS in patients with recurrent CHS was significantly lower than that in patients with primary CHS on admission (p = 0.05). Conclusions The combined posterior median and Wiltse approach is a technically viable option for en bloc resection of thoracic spinal CHS with huge paravertebral mass, and can give a favorable local control of CHS. Level of evidence Level V.